REVITALISASI ETIKA REMAJA LABUHANBATU: ANALISIS SEMIOTIKA TARI PILANDOK TAKIAL-KIAL SEBAGAI PEDOMAN PERILAKU - Tri Rahma Dana; Andra Maulana Syachrendra; Adib Alriansyah; Andini Eka Syafitri (Smart Education, 2026)
Abstract: This study aims to explore the pedagogical values within the Pilandok Takial Kial dance as an instrument for revitalizing youth ethics in Labuhanbatu Regency. In the digital era, teenagers face challenges of moral degradation and identity crisis that distance them from their local cultural roots. This study employs a qualitative approach with descriptive-analytical methods using Roland Barthes' Semiotic theory. Data were collected through textual observation of movements, literature studies, and in-depth interviews with dance maestros and traditional leaders. The results show that the Pilandok dance is not merely an aesthetic representation of a mousedeer’s movements but a system of signs containing strategic moral messages. Symbols of vigilance (eyes), resilience (takial-kial feet), and manners (worship gestures) are manifestations of the